The tadpole of Scinax juncae Nunes & Pombal, 2010 (Anura, Hylidae) - de Almeida Mercês, Ednei; Juncá, Flora Acuña (Zootaxa, 2012)
Scinax juncae is a hylid frog inhabiting the forest edge in Atlantic Forest remnants in the southern State of Bahia, Brazil (Nunes & Pombal Jr. 2010). This specie is morphologically similar to Scinax auratus (Wied-Neuwied) and Scinax cretatus Nunes & Pombal Jr. (Nunes & Pombal Jr. 2010, 2011), both of them also inhabit the Atlantic Forest in the Northeast of Brazil. We describe herein the previously unknown tadpole of Scinax juncae and compare it with tadpoles of other species of Scinax ruber species group sensu Faivovich et al. (2005) distributed in the lowlands of the Atlantic Forest (Nunes & Pombal Jr. 2010).